ECONOMIC AND MATHEMATICAL MODELING OF THE STRATEGIC DEVELOPMENT OF A HEALTHCARE INSTITUTION: CONCEPT BUILDING - NYTKA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The study revealed the relevance of the issue of economic and mathematical modeling of the strategic development of business entities specializing in the provision of services. The purpose of the study is to further develop the conceptual foundations of economic and mathematical modeling of the strategic development of health care institutions. It was concluded that the introduction of work on economic and mathematical modeling of their strategic development at health care institutions allows to significantly increase the effectiveness of the functioning of institutions, as it contributes to more careful planning of the main components of financial and economic activity. It has been proven that strategic plans for the development of health care institutions should be based on economic calculations of the necessary resource provision, evaluation of the effectiveness of operations and investment of funds, the value of economic security, as well as the calculation of the payback period of capital investments. The economic-mathematical model of the strategic development of the health care institution is defined and presented. It is proposed to interpret it as a set of elements that characterize the fundamental logic of its functioning, different from competitors, based on the use of key competencies for the most effective distribution of strategic resources in the system of business processes in order to provide services that meet the priorities of consumers. Elements of the Concept of an economic-mathematical model of the strategic development of health care institutions have been developed. The main idea of strategic development is the prediction of possible changes in the main parameters of the environment, modeling of the new market situation and directing resources to the transformation of activities in order to achieve maximum compliance with future conditions.
Keywords: health care institutions; strategic development; economic and mathematical modeling; methods; models; conceptual provisions